The Quest Of Meaning In Postmodern Era: Ken Carpenter’s Spiritual Crisis In Man From Nebraska - Mulyana, Yuli; Moelier, Dahlia D.; Mustakim, Rezki Amalia Wahyuni (Fakultas Sastra, Universitas Bosowa, 2025)
This research aims to explore the spiritual crisis faced by Ken Carpenter, the main character in Man from Nebraska, as a reflection of the confusion and loss of meaning experienced by many people in the postmodern era. This study used a qualitative descriptive method and applies existentialism and postmodernism theories. The study shows how Ken’s crisis begins with inauthenticity and grows into an existential crisis that forces him to question his faith and identity. Through self-awareness and freedom, he learns to take responsibility, accepts life limits, and finally reaches authenticity, where he embraces himself and finds new meaning in life.This change represents a personal and spiritual transformation. Man from Nebraska gives a picture of how modern people struggle to find meaning in a world where old beliefs no longer feel certain, while also showing how literature can reflect real life spiritual problems in today’s society.